First-line carboplatin plus pemetrexed with pemetrexed maintenance in HIV-positive patients with advanced non-squamous non-small cell lung cancer: the phase II IFCT-1001 CHIVA trial. Issue 2 (27th August 2020) - Lavole, Armelle; Greillier, Laurent; Mazières, Julien; Monnet, Isabelle; Kiakouama-Maleka, Lize; Quantin, Xavier; Spano, Jean Philippe; Lena, Herve; Fraisse, Philippe; Janicot, Henri; Audigier-Valette, Clarisse; Langlais, Alexandra; et al.
HIV infection is an exclusion criterion in lung cancer trials. This multicentre phase II trial aimed to assess feasibility, efficacy and safety of first-line carboplatin plus pemetrexed (CaP) followed by pemetrexed (P) maintenance in people living with HIV (PLHIV) with advanced non-squamous non-small cell lung cancer (NS-NSCLC). Four cycles of CaP were followed by P-maintenance therapy in patients with Eastern Cooperative Oncology Group performance status ≤2. The primary objective was a disease control rate (DCR) ≥30% after 12 weeks. Of the 61 PLHIV enrolled, 49 (80%) had a performance status of 0–1, and 19 (31%) had brain metastases. Median CD4 lymphocyte count was 418 cells·µL −1 (range 18–1230), median CD4 lymphocyte nadir was 169.5 cells·µL −1 (1–822); 48 (80%) patients were virologically controlled. Four-cycle inductions were achieved by 38 (62%) patients, and 31 (51%) started P-maintenance (median of 4.1 cycles (range 1–19)). The 12-week DCR was 50.8% (95% CI 38.3–63.4) and partial response rate 21.3%. Median progression-free survival and overall survival were 3.5 (95% CI 2.7–4.4) and 7.6 months (5.7–12.8), respectively. Patients with a performance status of 0–1 had the longest median progression-free survival (4.3 months, 95% CI 3.1–5.2) and overall survival (11.9 months, 95% CI 6.4–14.3). During induction, CaP doublet was well tolerated apart from grade 3–4 haematological toxicities (neutropenia 53.8%; thrombocytopenia 35.0%; anaemia 30.0%). Two fatal treatment-related sepses were reported. No opportunistic infections were experienced. In PLHIV with advanced NS-NSCLC, first-line four-cycle CaP induction followed by P-maintenance was effective and reasonably well-tolerated. Further studies should evaluate combination strategies of CaP with immunotherapy in PLHIV. In this first clinical trial dedicated to people living with HIV and advanced non-squamous non-small cell lung cancer, first-line 4-cycle carboplatin plus pemetrexed followed by pemetrexed maintenance chemotherapy was effective and reasonably well-tolerated https://bit.ly/2xAqeEl